2010
DOI: 10.1016/s2255-4971(15)30361-x
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis Diagnosis and Treatment

Abstract: Articles that update the state of knowledge regarding osteoporosis run the risk of quickly becoming obsolete because research and studies on osteoporosis today are arousing great interest among researchers, the pharmaceutical and medical equipment industries, governments and even WHO. All orthopedists know about osteoporosis because of its most deleterious effect: osteoporotic fracture. Osteoporosis without fractures does not arouse suspicion because this is a pathological condition with a nonspecific clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
10

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 31 publications
1
18
0
10
Order By: Relevance
“…Baron et al 16 found a predominance of this type of fracture among those between 50 and 70 years, especially in females after menacme. The incidence of non-vertebral fractures in several studies is higher in the femur, radius and humerus, 17 similar to our study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Baron et al 16 found a predominance of this type of fracture among those between 50 and 70 years, especially in females after menacme. The incidence of non-vertebral fractures in several studies is higher in the femur, radius and humerus, 17 similar to our study.…”
Section: Discussionsupporting
confidence: 92%
“…Pinheiro et al 4 show that sedentary lifestyle is among the main risk factors for low impact fractures in both genders, which may be related to poor bone quality, as well as lower neuromuscular control (with a higher incidence of falls). 17 …”
Section: Discussionmentioning
confidence: 99%
“…7 Vitamin D deficiency reduces calcium absorption and, as a result, increases parathyroid hormone (PTH) levels, which increases serum calcium levels, diminishes phosphate levels, increases osteoclasts activities, and, therefore, exacerbates osteopenia and osteoporosis. 8 9 As such, evidences show that vitamin D deficiency relates to a reduction in bone mineral density even in healthy populations. Moreover, the reduced muscle strength in the elderly increases their risk of fall.…”
Section: Introductionmentioning
confidence: 99%
“…7 A deficiência da vitamina D causa diminuição da absorção de cálcio e consequentemente aumento do PTH, o que eleva o cálcio sérico e diminui o fosfato, aumenta a atividade dos osteoclastos e, portanto, exacerba a osteopenia e osteoporose. 8 9 De tal modo, evidências apontam estar relacionada a uma diminuição da densidade mineral óssea mesmo na população saudável. Além disso, nos idosos a força muscular está diminuída, o que aumenta o risco de quedas.…”
Section: Introductionunclassified
“…Diminished bone mass and advanced age can be considered to be two of the main risk factors for fractures 2 . Bone fractures are one of the main causes of morbidity, mortality and hospitalization among the elderly and represent one of the biggest public health problems 3 .…”
Section: Introductionmentioning
confidence: 99%